The Impact of the Appeal on the Implementation of Judgments Decisions and Judicial Orders in UAE Law - Mariam Ahmed AL Sandal, (Journal of Legal Sciences, 2024)
The methods of appeal are divided into an ordinary appeal path, an unusual appeal path, and the only ordinary appeal method in the United Arab Emirates is appeal, and because of the diversity of judges' decisions, the effects of appeal on implementation varied, the study dealt with the impact of appeal on the implementation of judicial rulings, judicial decisions and judicial orders. The study addressed the topic in three sections: the first on the impact of appeals on judgments, the second on the impact of appeals on decisions, and the third on the impact of appeals on orders, using the descriptive-analytical method. The effects of appeals on execution are unclear due to the diversity of judicial actions issued by judges, and this is the motivation behind conducting the research. The study has reached important results, namely: there is an impact of appeal on the implementation of enforceable judgments, some of the execution judge's decisions, and it also affects performance orders. As for the most important recommendations, they include the necessity of amending some texts to align with the legislator's purpose.